Collateral damage of fipronil in economic and ecologically important non-target species - Villar, David; Schaeffer, David J (Revista Colombiana de Ciencias Pecuarias, 2022)
Fipronil is an insecticide and acaricide widely used in agriculture and domestic animals worldwide. Ecotoxicology studies have shown that, even at the low concentrations used on target species, fipronil and its degradation products have a significant impact on non-target species, either by direct toxicity or indirect effects affecting the food chain. The negative effects of fipronil on non-target species of terrestrial and aquatic invertebrates and indirect effects on food chains have led to its use being banned or severely restricted in numerous countries, including all of the European Union, China, and the United States. Some of the species highly susceptible to fipronil are of great economic and ecological importance, including crayfish, brown shrimp, and bees. In particular, the impact on decimating bee hives worldwide is an example of fipronil´s undesirable effects on agriculture. Other species affected by fipronil -for which there are few studies- are biological predators of the same pests controlled by fipronil. Considering all the impacts on non-target species, the commercialization and indiscriminate use of fipronil in agriculture seem irresponsible. In Colombia, as of September 2021 and pressed by local beekeepers, the Instituto Colombiano Agropecuario (ICA) prohibited its use on avocado, coffee, citrus, and passiflower plantations. However, as long as its use is not prohibited in all agricultural applications, farmers could divert its use and continue using it in any other type of plantation. This paper describes the impact of fipronil on some of the beneficial invertebrate species of outmost economic and ecological importance.